DIGITALISASI UMKM MELALUI PELATIHAN DAN PENGEMBANGAN WEBSITE E-COMMERCE PADA SUSI SEPRAI DAN BEDCOVER DI KOTA PADANG - Komalasari, Sanda Patrisia; Hadelina, Rizka (Jurnal Hilirisasi IPTEKS, 2025)
The aim of this activity is to assist in the digitalization of marketing for the MSME Susi Seprai and Bed Cover in Padang City through the creation and training in the use of an e-commerce website. This MSME faced declining sales due to the COVID-19 pandemic, requiring a strategy to expand market reach. The methodology used consisted of three main stages. First, identifying the partner’s needs through direct interviews with the business owner to understand the challenges and specific needs related to digital marketing. Second, creating an e-commerce website that functions as a product catalog with features such as online payment, product rating, and reviews. The website design was customized to be responsive and user-friendly for the owner, who has limited experience with technology. Third, training was conducted at the business location, covering content management, product uploads, payment system setup, and comment moderation. Despite the website’s completion and the training provided, its usage remains suboptimal. Key challenges include limited workforce, the advanced age of the owner, and a lack of experience in managing digital technologies. However, the website has the potential to support marketing efforts, expand market reach, and improve product visibility. The conclusion is that the success of utilizing the website depends on increasing the owner’s capacity and confidence in managing digital technology independently. Therefore, further intensive assistance is recommended, along with digital promotion through social media and search engine optimization (SEO) to improve marketing effectiveness and broaden the MSME’s market reach.